Analisis Persaingan Usaha Dalam Etika Bisnis Islam Di Kabupaten Jombang - Ririn Susilawati; Moh. Imsin; Khoirotun Nikmah (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2021)
The purpose of this study is to describe and analyze how business competition is between grocery store traders according to Islamic business ethics in Jombang Regency by using a qualitative descriptive method. The results show that the five aspects that affect the competitive power include the threat from new entrants to thegrocery store industry which is moderate, the threat from substitute products is quite strong, the bargaining power of suppliers is moderate, the bargaining power of buyers, and competitive competition in the market. between members of the industry are both strong. And the results of the competition in the grocery store business in theJombang Regency, in Islamic business ethics are categorized as healthy and unhealthy competition. For the healthy category, there are 80% store business actors who are in accordance with Islamic business ethics. As for the unhealthy category, there are 20% business actors who are not in accordance with Islamic business ethics.